Securing SQL Server. (September 2015) - Unknown
Abstract : The fact that this book is already in its third edition is a testament to an unfortunate truth – SQL databases are one of the most common ways to compromise websites and apps. In fact, there are all kinds of ways that hackers can find their way into databases – and, of course, that's where you keep your most precious data.